Classroom teaching skills - Irizarry, Jason G. (Wadsworth, Cengage Learning, 2014)
This tenth edition of Classroom Teaching Skills will help beginning teachers meld theory with practice. This book conceptualizes the effective teacher as a reflective decision maker, one who makes planning, implementing, evaluating, and management decisions as part of the instructional role --Preface.